2003
DOI: 10.1124/dmd.31.3.312
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein Limits the Brain Penetration of Nonsedating but not Sedating H1-Antagonists

Abstract: ABSTRACT:The present study evaluates the impact of P-glycoprotein (P-gp) on plasma-brain disposition and transepithelial transport of sedating versus nonsedating H1-antagonists using multidrug-resistant (mdr) gene 1a and 1b (mdr1a/b) knockout (KO) mice and human MDR1-transfected Madin-Darby canine kidney (MDCK) cells. Three nonsedating (cetirizine, loratadine, and desloratadine) and three sedating (diphenhydramine, hydroxyzine, and triprolidine) H1-antagonists were tested. Each compound was administered to KO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
147
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(161 citation statements)
references
References 27 publications
10
147
0
2
Order By: Relevance
“…The absence of a sedative effect of desloratadine may be explained by efficient efflux via P-gp, as demonstrated previously (Chen et al, 2003), that negates the uptake by the BCECs. Nonsedative fexofenadine was reported to show relatively low transport via P-gp, as evaluated in terms of the flux ratio of basal-to-apical/apical-to-basal transport in a monolayer of MDR1-expressing cells, although it is a substrate of P-gp (Cvetkovic et al, 1999).…”
Section: Bbb Transport Of Nonsedative H1-antagonist Epinastinementioning
confidence: 69%
See 2 more Smart Citations
“…The absence of a sedative effect of desloratadine may be explained by efficient efflux via P-gp, as demonstrated previously (Chen et al, 2003), that negates the uptake by the BCECs. Nonsedative fexofenadine was reported to show relatively low transport via P-gp, as evaluated in terms of the flux ratio of basal-to-apical/apical-to-basal transport in a monolayer of MDR1-expressing cells, although it is a substrate of P-gp (Cvetkovic et al, 1999).…”
Section: Bbb Transport Of Nonsedative H1-antagonist Epinastinementioning
confidence: 69%
“…Since the cationic derivatives also exhibit stronger sedative effects, the influx transporter was supposed to be a determinant of the sedative effect of H1-antagonists (Yamazaki et al, 1994a,b,c). Then, involvement of the efflux transporter P-gp as a determinant was proposed, and several studies found a positive correlation between the sedative effect and transport by P-gp (Cvetkovic et al, 1999;Tamai et al, 2000a;Chishty et al, 2001;Chen et al, 2003). Accordingly, both influx and efflux transporters should be important to determine the apparent brain distribution of H1-antagonists.…”
Section: Fig 2 Transepithelial Transport Of [ 14 C]epinastine (5 M)mentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting results of present study confirm the idea. On the other hand, previous studies demonstrated P-gp substrate role of the cetirizine in mice blood-brain barrier (BBB), 20 1b (mdr1a/b) knockout mice, 21 human MDR1-transfected Madin-Darby canine kidney cells, 21 and human Caco-2 cells 22 using monolayer efflux assay 20 and other in vitro and in situ assays. To the best of our knowledge, both digoxin and cetirizine are substrates of P-gp and competition for binding sites of P-gp molecules by them is suggested.…”
Section: Discussionmentioning
confidence: 99%
“…A major reason for the reduced penetration of second-generation H 1 -antihistamines into the brain is because their translocation across the blood-brain barrier is under the control of active transporter proteins, of which the ATP-dependent efflux pump, P-glycoprotein, is the best known[50,51]. It also became apparent that antihistamines differ in their substrate specificity for P-glycoprotein, fexofenadine being a particularly good substrate[52].…”
Section: Second-generation H1-antihistaminesmentioning
confidence: 99%